Assessment of some heavy metal content in sediments of a mangrove swamp, niger delta, nigeria using applicable ecological risk indices - Chris, Davies Ibienebo; Anyanwu, Emeka Donald (Acta Aquatica: Aquatic Sciences Journal, 2023)
Sediments can act as pollutant sinks and a source of pollution in aquatic environments. The surface sediments of the Isaka-Bundu tidal swamp, Niger Delta was assessed for heavy metal content using standard methods and assessment indices. The study was carried out in three stations between January and June 2022. Five heavy metals (lead, copper, cadmium, nickel and zinc) were evaluated while eight assessment indices (Contamination Factor - CF, degree of contamination - DC, Ecological Risk - Er, Potential Ecological Risk - PERI, Pollution Load Index - PLI, Enrichment Factor - EF, Geo-accumulation Index - Igeo and Quantification of Contamination -QoC) were applied. Results showed that cadmium and copper exceeded permissible limits while lead, zinc and nickel were within limits. Stations 1 and 3 recorded significantly higher values indicating anthropogenic influence. The dominant anthropogenic activities observed in the area include maritime and dockyard activities and artisanal crude oil refinery. The assessment indices showed that the sediments were at various levels of heavy metal pollution mainly influenced by copper and cadmium viz: CF: Cu (considerable degree) and Cd (very high degree), DC (very high degree), Er: Cd (high ecological risk) and Cu (very high ecological risk), PERI (significant high ecological risk), PLI (very high level pollution), EF: Pb, Zn, Cu (Station 1) and all Cd (extremely high enrichment), Igeo:  Cd (extremely polluted) and QoC: Cu and Cd (anthropogenic source). The sediments were highly polluted with toxic metals, which is detrimental to humans and aquatic biota.Keywords: Heavy metal; Indices; Mangrove; Niger Delta; Sediment.